Greenland, Hisinger Glaciers at Goodenough Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 27 - Looking over the terminus of Hisinger Glacier into Dickson Fiord from the northern side. This was the farthest point reached overland from Kjerulf Fiord. Note the distinctive landmark in the ice cap of the mountains in the background and campare Figure 19. August 2, 1931. (Caption from Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Fiords. Geographical Review, 22(4), 549.) Fiord region of East Greenland Boyd, L. A. (1932). Fiords of East Greenland: A Photographic Reconnaissance throughout the Franz Josef and King Oscar Flords. Geographical Review, 22(4), 529-561.